2006
DOI: 10.1074/jbc.m510383200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Receptor Activator of NF-κB (RANK) Cytoplasmic Motif Plays an Essential Role in Osteoclastogenesis by Committing Macrophages to the Osteoclast Lineage

Abstract: Receptor activator of NF-B (RANK) ligand (RANKL) and its receptor RANK play an essential role in osteoclastogenesis and osteoclast function by activating several signaling pathways. However, several lines of evidence suggest that RANK also transmits an unidentified signaling pathway(s) essential for osteoclastogenesis. To identify the novel pathway(s), we carried out a detailed structure/function study of the RANK cytoplasmic domain. A series of studies using numerous deletion/point mutants elucidated a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 59 publications
5
59
0
1
Order By: Relevance
“…Thirdly, RANK cytoplasmic domain shares no homology with any known members of the TNFR family (74), further suggesting that it may activate downstream signals different from those arising from other members of the TNFR family. A systematic structure/function study of the RANK cytoplasmic domain has identified a specific 4-a.a. RANK motif (IVVY535-538), which function to mediate commitment of macrophages to the osteoclast lineage in osteoclastogenesis (119). This finding is consistent with the previous study that RANKL plays an essential role in committing macrophages to the osteoclast lineage (120).…”
Section: Rankl Rank and Osteoprotegrin (Opg)supporting
confidence: 82%
“…Thirdly, RANK cytoplasmic domain shares no homology with any known members of the TNFR family (74), further suggesting that it may activate downstream signals different from those arising from other members of the TNFR family. A systematic structure/function study of the RANK cytoplasmic domain has identified a specific 4-a.a. RANK motif (IVVY535-538), which function to mediate commitment of macrophages to the osteoclast lineage in osteoclastogenesis (119). This finding is consistent with the previous study that RANKL plays an essential role in committing macrophages to the osteoclast lineage (120).…”
Section: Rankl Rank and Osteoprotegrin (Opg)supporting
confidence: 82%
“…9B, left panel). Similar to previous reports that both T6BSs and the IVVY motif are crucial for osteoclastogenesis (12,13,16,17), OC formation was not detected in hCD40/ mRK mutants that lacked either T6BSs (hCD40/mRK-AAA) or the IVVY motif (hCD40/mRK-LAAF) after 3-day culture (Fig. 9B, left panel).…”
Section: The Traf6-vav3 Interaction Enhances Osteoclastogenesis-supporting
confidence: 75%
“…Studies of deletion mutations of RANK cyto have revealed that RANK cyto harbors a unique domain named the highly conserved domain in RANK (HCR, amino acids 487-546) that functions as a crucial regulatory motif in RANK-mediated osteoclastogenesis (16,17). Upon RANKL stimulation, HCR recruits additional adaptor/kinase molecules, such as Vav3, Grb-2-associated binder 2 (Gab2), and phospholipase C ␥2 (PLC␥2), to induce the late phase of RANK-mediated signaling (16,18,19).…”
mentioning
confidence: 99%
“…To overcome this issue, we have characterized a signaling pathway that is initiated by a specific motif of RANK (27). While point mutation analyses suggested that this motif might play an important role in OC differentiation in vitro, how it regulates OC formation or whether this motif is also important for the fate of OC in vivo has not been investigated.…”
Section: Introductionmentioning
confidence: 99%